Lesotho : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Joint Staff Assessment examines the Poverty Reduction Strategy Paper (PRSP) Progress Report for Lesotho. Poverty monitoring and the medium-term macroeconomic framework are areas in which the government has made considerable progress. The government has taken a number of steps to ensure that the PRSP will be completed and presented to the IMF and World Bank by November 2003. The report indicates that the government and participating donors have guaranteed sufficient funds to complete the PRSP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: CR; ISCR; PRSP Indicator; PRSP Preparation Status Report; PRSP Process; Lesotho, Kingdom of